Optimalisasi Layanan Bengkel Desa Melalui Sistem Stok Manajemen Berbasis Web dan Kartu Nama - Dia Puspitasari; Mohammad Rafly; Rista Intan; Prisca Ambarwati; Andri Hermawan; Riska Putri Dinarti (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2025)
Many small auto repair businesses struggle with promotion and managing their operations efficiently. IY AutoPlus Workshop is one of them, still relying on manual systems and lacking digital promotion. This community service project aimed to help the workshop become more well-known and operate more efficiently. The team created business cards, flyers, and a website for service booking and stock management. As a result, the workshop’s promotion reached more people, inventory was better organized, and customers found it easier to access services. With digital technology, the workshop has a better chance to grow and compete in today’s market